ASSESSMENT OF RENAL GRAFT FUNCTION DEPENDING ON PRE-TRANSPLANT MORPHOLOGY - Lubuska, Lucie; Bachleda, Petr; Tichy, Tomas; Lubusky, Marek; Utikal, Petr; Hrabalova, Monika; Chudacek, Josef; Janout, Vladimir (Biomedical papers, 2006)
Background: Histopathological assessment of kidney prior to transplantation is a part of the comprehensive information gathered on the transplanted organ. In our study we monitor the influence of individual morphological findings (glomeruli, arteries, arterioles, interstitium, tubules) and degree of histopathological changes in the kidney function after transplantation.Methods: From 1994 to 1997, 117 cadaveric kidneys were histopathologically examined and subsequently transplanted. Biopsy in a form of wedge excision was obtained during the organ procurement after in situ kidney perfusion and its removal from donor's body. Evaluated were glomerulosclerosis, intimal fibrosis of arteries, arteriolar hyalinization, interstitial fibrosis and tubular changes (vacuolar dystrophy of tubular epithelium, desquamation of tubular epithelium, brush border of proximal tubules, tubular dilatation, haemoglobin cylinders in distal tubules). Kidney recipients were monitored both for immediate function of transplanted organ and long-term kidney function for a period of five years following.Results: In our group of patients, no unambiguously negative influence of histopathological change in individual morphologies was found either in the immediate or in the long-term function of the transplanted kidney.Conclusion: It is possible to transplant kidneys and attain satisfactory results even with these types of histopathological changes: glomerulosclerosis greater or equal to 20 %, mild degree of arterial lesion, moderate arteriolar lesions, moderate lesions of interstitial fibrosis and tubular lesions. The degree of arterial lesions, arteriolar lesions and the degree of interstitial fibrosis closely correlate to the donor's age, hypertension and nontraumatic cerebrovascular accident as the cause of death. Same outcomes were also confirmed with glomerulosclerosis, with the exception of the influence of the donor's age.
Keywords: Kidney transplantation/Pre-transplant wedge renal biopsy/Glomerulosclerosis/Arteriolar hyalinisation/Arterial